The Utilization of Achatina fulica Mucus in Alginate Membrane as Wound Healing Accelerator and Anti- Infection Material - Rahmawati, Fatkhunisa; Mayasari, Dita Ayu; Adhitioso, Satrio; Putra, Alfian Pramudita; Kuntjoro, Eko Budi; Widiyanti, Prihartini (Indonesian Journal of Tropical and Infectious Disease, 2014)
Wound should be covered with bandage that is called wound dressing. Most people use synthetic materials such as gauze dressing. Gauze has high absorption of NaCl, which is often used to cleanse the wound. However, discomfort and pain arise since the gauze becomes sticky on the wound. Therefore, we need other alternatives instead of gauze to cover wound. One such alternative is the alginate membrane. This study used alginate membrane with mixture of mucous of the snail Achatina fulica, which contain proteins such as proline, serine asparagine, glycosaminoglycan, hydroxylysine, trionin and so forth, to activate the growth factor. Alginatepowder and carboxymethl cellulose (CMC) was dissolved in distilled water mixed with mucus of the snail Achatina fulica in four variations (4:0; 4:1, 4:2, 4:3) through a magnetic stirrer, and casted on a baking sheet covered with sterile gauze. High Performance Liquid Chromatography (HPLC) test showed that the glycosaminoglycan content was found on the mucous of Achatina fulica. This was indicated by the appearance of peak at 325–350 second. The most optimum alginate and mucus composition was in ratio of 4:2. This ratio resulted in a wound dressing that was still able to absorb the exudate and optimally accelerated wound healing.